(untitled) - Connors, Michae (Oxford, UK, 1997)
Infostructure change is technology-driven, inevitable, somewhat predictable and, on the whole, beneficial. But it will also be much more disruptive than we realise and it will change the World Order.
Keywords: Information technology,Information technology,Twenty-first century,Công nghệ thông tin,Công nghệ thông tin,Thế kỷ 21; Economic aspects,Forecasting,Social aspects,Forecasting,Forecasting,Khía cạnh kinh tế,Dự báo,Khía cạnh xã hội,Dự báo,Dự báo